2023
DOI: 10.1002/jsfa.12442
|View full text |Cite
|
Sign up to set email alerts
|

Stale bread waste recycling as ingredient for fresh oven‐baked white bread: effects on dough viscoelasticity, bread molecular organization, texture, and starch digestibility

Abstract: BACKGROUND Wasted food produced for human consumption is estimated at 33% globally, and bread is the food product with the highest percentage. There is an ongoing drive to reincorporate food waste still useful and safe into the production chain of food for human consumption. This work aims to contribute to the study of the feasibility of recycling stale bread waste flour (BWF) into fresh oven‐baked white bread, by replacing 0, 20, 40, 60, 80, and 100 g/100 g of the wheat flour with BWF. RESULTS Storage and los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Taking this into account, it can be concluded that the P2 formulation added in amounts of less than 15% did not cause a clear difference in the color of the crumb of the bread samples with their share compared with the standard, while even a minimal share of the P1 formulation would be noticeable by consumers. The change in color is partly due to the use of the recycled bread share, as well as the share of apple pomace, which generally modifies the color of bread [10,61]. But it may also be a result of the lower porosity and volume of the bread samples, as, in general, the crumb is darker the lower its porosity [62], which was also observed in the study of this work.…”
Section: The Effect Of Extruded Preparations On the Texture And Physi...supporting
confidence: 75%
See 3 more Smart Citations
“…Taking this into account, it can be concluded that the P2 formulation added in amounts of less than 15% did not cause a clear difference in the color of the crumb of the bread samples with their share compared with the standard, while even a minimal share of the P1 formulation would be noticeable by consumers. The change in color is partly due to the use of the recycled bread share, as well as the share of apple pomace, which generally modifies the color of bread [10,61]. But it may also be a result of the lower porosity and volume of the bread samples, as, in general, the crumb is darker the lower its porosity [62], which was also observed in the study of this work.…”
Section: The Effect Of Extruded Preparations On the Texture And Physi...supporting
confidence: 75%
“…The use of flour obtained from dried bread in baking has been studied earlier [ 10 , 11 , 55 ], but those studies focused on obtaining light-colored bread. It was found that with the increase in the share of dried bread, in general, worse quality characteristics (lower volume, worse texture) and, above all, a deterioration in the color of the product were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study has examined the effect of replacing a portion of wheat flour with chickpea protein concentrates in bread production. The results indicated that the bulk bread volume made with 6% and 9% chickpea protein was greater than that of the control bread made entirely with wheat flour, although the magnitude of the increase was less pronounced compared to the control [171]. The authors documented that the reduced water vapor production observed during bread baking could be responsible for the elevated water absorption capacity of plant-based proteins [172].…”
Section: Application Of Chickpea Protein: Food Industrymentioning
confidence: 98%